Sacrifice in the ancient Mediterranean: recent and current research - Ullucci, Daniel C. (Currents in biblical research, 2015)
This essay provides a summary and critical assessment of scholarship on sacrifice in the ancient Mediterranean over the last two decades. It focuses on Greek, Roman, Judean and Christian evidence from approximately the eighth century bce to the fifth century ce. Significant attention is paid to theoretical models, which have deeply affected the study of sacrifice. Archeological evidence for sacrifice is considered. The following areas of current scholarly debate are addressed and assessed: (1) the reach and role of religious experts; (2) sacrifice as communication and failed sacrifice; (3) the notion of spiritualization; (4) metaphorical and symbolic uses of sacrifice; and (5) sacrifice and identity. Sacrifice is theorized not as a static category or ontological thing, but a nexus of competitive ritualizations and/or discursive claims, the boundaries of which were actively contested by ancient practitioners and cultural producers.